Ein neuer griechischer Stenus aus dem Deutschen Entomologischen Institut Eberswalde. 74. Beitrag zur Kenntnis der Steninen (Coleoptera: Staphylinidae). - Puthz, Volker (Contributions to Entomology = Beiträge zur Entomologie, 1970)
A new species from Greece is described which belongs to the monophyletic group of Stenus fossulatus-guttula. A detailed comparison to Stenus bosnicus Bernhauer is given, also a description of its hitherto unknown edeage. Also the first Stenus-edeage is published which is monstrous.Nomenclatural Actssacrimontis Puthz, 1970 (Stenus (Stenus)), spec. n.